Circularly polarized luminescence of agglomerate emitters. Issue 5 (3rd May 2021) - Zhang, Chong; Li, Si; Dong, Xi‐Yan; Zang, Shuang‐Quan
Abstract: Circularly polarized luminescence (CPL) originates from the chiral emissive excited states. CPL materials have promising applications in 3D optical displays, encryptions, biological probes, chiral photoelectric devices, and CPL switches, most of which require excellent CPL performances including bright luminescence and high luminescence dissymmetry factor ( g lum ) in the agglomerate state. This review systematically summarizes the progress about CPL of aggregate and solid materials, such as organic materials, metal‐organic materials (such as coordination polymers, organic‐inorganic metal halides, metal clusters, and cluster‐assembled materials), the assembled materials by supramolecular interactions, and liquid crystals. We also present the current challenges and a future perspective of chiral emitting agglomerate materials. Abstract : In this review, besides the fundamental principles of circularly polarized luminescence (CPL), CPL measurement methods for solid‐state samples and the recent progress of the diverse agglomerate CPL‐emitters, including organic materials, crystalline metal‐organic materials (coordination polymers, organic–inorganic metal halides, metal clusters, and cluster‐assembled materials), supramolecular ensembles, and liquid crystals are summarized. The opportunities and challenges of CPL‐emitters in agglomerate state are presented.